Understanding Customer Service Quality and Customer Loyalty of Internet Banking In Private and Public Sector Banks - Mann, B.S.; Sahni, Sunpreet (Gyan Management Journal, 2008)
As Private and Public sector banks arc providing Internet Banking services, understanding the dynamics of customer's usage of products and rvices and evaluating the customer service quality and customer loyalty level becomes a key priority. The demographic profile of the active users oflnternetBanking was studied in-depth. The influential sources of information from where the customers become aware regarding Internet Banking have been identified. The major financial products and services were calculated pertaining to Private and Public sector banks. Customer service quality provided b the Private and Public sector Inlerne Banks has been gauged and the findings reveal that Private sector banks excel as compared to the Public sector banks. Further, it can be substantiated from the findings that customer loyalty level is more in Private Banks as compared to public sector banks.
Keywords: Customer Service Quality; Customer Loyalty; Internet Banking; Private and Public Sector Banks